Analysis of the life-cycle cost and capability trade-offs associated with the procurement and sustainment of open systems. (21st June 2022) - Chen, Shao-Peng; Sandborn, Peter; Lucyshyn, William
System openness refers to the extent to which system components (e.g., hardware and software) can be independently integrated, removed, or replaced without adversely impacting the existing system. Openness is an intuitively understood concept used to describe the architecture and implementation of safety-, mission- and infrastructure-critical systems. While openness is widely associated with life-cycle cost avoidance, system openness can also lead to increased costs in some cases. Previous efforts to establish value have relied on qualitative system analyses, with the results often articulated as an intangible 'openness score' that fails to provide the information necessary to understand the conditions under which there is a life-cycle cost avoidance. This paper develops a model that quantifies the relationship between system openness, life-cycle cost and system capability risks. A case study that evaluates the acoustic rapid COTS insertion (A-RCI) Sonar System is provided.